Antioxidant and antibacterial activities of alkaloids from endophytic bacterium Pseudomonas hibiscicola Wk isolated from waru (Hibiscus tiliaceus) leaves - Sarjono, Purbowatiningrum Ria; Laksmitasari, Nuraini Dwi; Asy'ari, Mukhammad; Ngadiwiyana, Ngadiwiyana; Ismiyarto, Ismiyarto; Fachriyah, Enny (Universitas Negeri Yogyakarta, 2025)
This study aims to investigate the antioxidant and antibacterial activity from alkaloid extract. Alkaloid compounds were isolated from the endophytic bacteria Pseudomonas hibiscicola Wk, which was obtained from Hibiscus leaves. The alkaloid compounds were characterized using thin layer chromatography. The isolated alkaloid compounds were tested for total phenol content, and antioxidant activity. The phytochemical analysis of the alkaloid compounds from the endophytic bacteria Pseudomonas hibiscicola Wk showed a positive result for alkaloids, confirmed by an Rf value of 0.8125 which is similar to the Rf value of alkaloids from the periwinkle plant, namely vindoline (Rf = 0.85). Alkaloid compounds from the endophytic bacteria Pseudomonas hibiscicola Wk had the highest total phenol content of 2.390 mg gallic acid/gram sample at a concentration of 10.000 mg/L. These results indicate that the alkaloid compounds obtained contain phenol groups. The IC50 value obtained from the isolated alkaloid compound was 99.70 mg/L, demonstrating strong antioxidant capacity, and has the ability to inhibit the growth of E.coli and S.aureus bacterial.